2021
DOI: 10.1002/app.51382
|View full text |Cite
|
Sign up to set email alerts
|

Catechol‐containing waterborne polyurethane adhesive inspired by mussel proteins

Abstract: A series of waterborne polyurethane (PDMAPU) containing catechol group were prepared by double-bond random copolymerization of terminated double bond polyurethane prepolymer with modified acrylamido dopamine under thermal initiation. This kind of mussel-like waterborne polyurethane adhesive is inspired by marine mussel, as well as it is environment-friendly and used in bonding of leather. FTIR and 1 H NMR proved the successful introduction of catechol group into polyurethane matrix. Oxidative cross-linking bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Firstly, GDML containing epoxy groups and catechol groups can react with the CONH, OH, and NH 2 groups in PA66. During the co‐vulcanization process, the highly reactive catechol groups in GDML are oxidized to form ortho‐quinone and di‐quinone structures, which can further crosslink with the amino groups in PA66 by Schiff base or Michael addition reactions 38 . Secondly, the epoxy group crosslinks with the ‐CONH‐ group to form a chemical bond at 150°C 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, GDML containing epoxy groups and catechol groups can react with the CONH, OH, and NH 2 groups in PA66. During the co‐vulcanization process, the highly reactive catechol groups in GDML are oxidized to form ortho‐quinone and di‐quinone structures, which can further crosslink with the amino groups in PA66 by Schiff base or Michael addition reactions 38 . Secondly, the epoxy group crosslinks with the ‐CONH‐ group to form a chemical bond at 150°C 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, matt coatings are widely used on the surfaces of wood and furniture, leather accessories, automotive parts, aircra shells, electronic equipment shells, school and hospital wall surfaces and so on. 2,[7][8][9][10][11] With the global emphasis on environmental protection concepts, volatile organic solvent (VOC) emission standards are becoming more and more stringent. [12][13][14][15][16] Waterborne polyurethane (WPU) is a polyurethane resin with water as dispersion medium.…”
Section: Introductionmentioning
confidence: 99%
“…11 WPU not only has the advantages of traditional solvent-based polyurethane, such as excellent wear resistance and mechanical properties, but also is environmentally friendly, safe and reliable. 10,12,17 Therefore, it is widely used in coatings, adhesives, leather nishing agents and inks. 9,18,19 The principle of obtaining low gloss coating is that the rough surface has microscopic protrusions and depressions.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon-borane fluorinated polyesters (CFPETs) and polyurethanes (CFPUs) were characterized, and the results demonstrated that the modified polyurethanes had better features, including heat resistance and solvent resistance. Ren et al created a variety of aqueous polyurethanes containing catechol (PDMAPU) using heat-initiation copolymerization of modified acrylamide and polyurethane prepolymer. The oxidative cross-linking of catechol structures inside the PDMAPU structure increased the material’s thermal stability and crystallization potential.…”
Section: Introductionmentioning
confidence: 99%
“…Also, many studies have been done in an effort to increase the heat resistance of a waterborne polyurethane pressure sensitive adhesive. Fu et al 16 Ren et al 18 created a variety of aqueous polyurethanes containing catechol (PDMAPU) using heat-initiation copolymerization of modified acrylamide and polyurethane prepolymer. The oxidative cross-linking of catechol structures inside the PDMAPU structure increased the material's thermal stability and crystallization potential.…”
Section: ■ Introductionmentioning
confidence: 99%